2017
DOI: 10.1111/cei.12984
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D treatment modulates immune activation in cystic fibrosis

Abstract: Persistent inflammatory response in cystic fibrosis (CF) airways is believed to play a central role in the progression of lung damage. Anti-inflammatory treatment may slow lung disease progression, but adverse side effects have limited its use. Vitamin D has immunoregulatory properties. We randomized 16 CF patients to receive vitamin D2, vitamin D3 or to serve as controls, and investigated the effect of vitamin D supplementation on soluble immunological parameters, myeloid dendritic cells (mDCs) and T cell act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 60 publications
1
39
0
1
Order By: Relevance
“…The most trails which have shown reduction of inflammation and improved lung function in CF patient have administered at least a double dose (above 2000 IU) of cholecalciferol [25, 26]. Pincikova et al [27]. randomized CF patients to receive 35,000–50,000 IU vitamin D per week for three months and observed that this supplementation has pleiotropic immunomodulatory effects in CF in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The most trails which have shown reduction of inflammation and improved lung function in CF patient have administered at least a double dose (above 2000 IU) of cholecalciferol [25, 26]. Pincikova et al [27]. randomized CF patients to receive 35,000–50,000 IU vitamin D per week for three months and observed that this supplementation has pleiotropic immunomodulatory effects in CF in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of IL-1b, IL-6, IL-8, tumor necrosis factor, transforming growth factor-b, IL-10, IL-17, interferonl-inducible protein 10, monocyte chemoattractant protein-1, IL-7, IL-18, IgG, IgM, IgA, and IgE were within the normal range (not shown). Frequencies of natural killer cells, B cells, T cells, regulatory T cells, and invariant natural killer T (iNKT) cells were normal (Table 1) 3 ; however, mucosal-associated invariant T (MAIT) cells were strikingly undetectable on three different occasions (Table 1 and Fig 1A). 3 In contrast, normal MAIT cell levels were detected in healthy donors as well as in matched patients with CF ( Fig 1A).…”
Section: Case Reportmentioning
confidence: 99%
“…Frequencies of natural killer cells, B cells, T cells, regulatory T cells, and invariant natural killer T (iNKT) cells were normal (Table 1) 3 ; however, mucosal-associated invariant T (MAIT) cells were strikingly undetectable on three different occasions (Table 1 and Fig 1A). 3 In contrast, normal MAIT cell levels were detected in healthy donors as well as in matched patients with CF ( Fig 1A). The patient's father and sister had normal levels, whereas his mother had one log lower than normal MAIT cell frequency ( Fig 1B).…”
Section: Case Reportmentioning
confidence: 99%
“…The specific mechanism was still not well understood. Nonetheless, as vitamin D could lower plasma erythropoietin levels, we hypothesized that the breakdown of fetal erythrocytes might be decelerated through this route so that the negative correlation between 25(OH)D and IBIL/TBIL was observed (23). On the other hand, evidence had shown that normal newborn erythrocytes were relatively sensitive to oxidative damage (24).…”
Section: (Oh)d and Jaundice In Neonatesmentioning
confidence: 99%